Species Diversity and Distribution of Orchids along the Sepapah Kiri Waterfall Trail, Kubu Perahu, Bukit Barisan Selatan National Park - Kurniasih, Surti; Prasaja, Dimas (Biota, 2026)
Indonesia is known as a country with a high diversity of orchids. Bukit Barisan Selatan National Park (BBSNP) is located along the Bukit Barisan Mountain range in the tropical rainforest heritage of Sumatera, where various natural-growing orchids can be found abundantly. This study aimed to explore and identify the orchids diversity in the Kubu Perahu Forest section of Bukit Barisan Selatan National Park. The observation was conducted along the hiking trails of Sepapah Kiri Waterfall, which has a 2.375 m length and about 568-876 masl. An exploratory method was conducted to collect primary and environmental data. A total of 16 genera were recorded, dominated by epiphytic orchids, with Agrostophyllum and Pinalia as the most abundant genera. Preservation of natural orchid species is needed by cultivation and increasing the exsitu conservation of orchids.